Efeito do jejum no período ativo sobre humor e comportamento alimentar de mulheres magras e obesas - Jenneffer Rayane Braga Tibaes (2019)
Introduction: Fasting is a historical practice derived from different ideological and religious traditions, but it has now also been popularized as a dietary strategy to reduce body weight. Objective: To investigate the effect of fasting on mood, subjective feelings of satiety, food cravings and food intake in lean and obese individuals. Methods: This is a non-randomized clinical trial stratified by nutritional status. The sample consisted of adult women (18 to 60 years of age), divided into two groups according to Body Mass Index (BMI): lean group (BMI > 18.5 kg/m² and < 24.99 kg/m²) and obese group (BMI > 35 kg/m²). The initial evaluation was performed in the morning after 10h of nocturnal fasting. A structured questionnaire was used to obtain socioeconomic, health and food consumption data. Data collection consisted of anthropometric evaluation, body composition, resting energy expenditure, food intake and questionnaires to evaluate the subjective feelings of satiety, food cravings and mood. Afterwards, standardized breakfast was offered and the volunteer was discharged for daily living activities while fasting for 10 hours. After this time, the volunteer returned to repeat the experimental procedures (anthropometry, calorimetry, body composition assessment and questionnaire application). Statistical analyses were carried out with the aid of Statistical Package for the Social Sciences for Windows Student Version® (SPSS) version 20.0 and GraphPad Prism version 5.0, adopting a significance level of 5%. Results: Fifty-four women were included in the study, 29 in the lean group and 25 in the obese group. The volunteers of the lean group presented increased scores in two of the five negative subscales of the Brunel Mood Scale: anger and fatigue, while the obese group presented increase in three negative subscales: anger, depression and fatigue. In both groups there was a reduction of the only positive subscale (vigor). However, there was no difference between group variations for mood. For the subjective feelings of satiety, in both groups there was an increase in hunger, a decrease in satiety and fullness, and an increase in prospective consumption. Hunger was the only different variable between the groups, with the highest increase in the obese group. The results of the food cravings questionnaire showed an increase in the intense desire for food only for the obese group. Caloric intake after daytime fasting was similar to the usual dietary intake prior to fasting. Conclusion: Daytime fasting performed concomitantly with daily living activities can alter mood and different aspects of eating behavior. Therefore, fasting dietary interventions should be applied cautiously in subjects with and without obesity